2022
DOI: 10.1585/pfr.17.1203077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geodesic Curvature on Zonal Flow Generation in Magnetically Conned Plasmas

Abstract: The impact of magnetic geometry on zonal-flow generation in ion temperature gradient driven turbulence is investigated by means of linear and nonlinear gyrokinetic simulations. The modulation of geodesic curvature on various configurations has revealed amplification of the zonal-flow intensity in relatively smaller geodesic curvature. Based on these findings, a nonlinear proxy model for explorations of novel magnetic geometry to activate the zonal-flow dynamics is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The zonal-flow effect significantly decreases with the geodesic curvature, whereas the scatter is large in the region of Z 1/2 /T < C 2 = 1.1 × 10 −2 . The dependence of the zonal-flow effect on the geodesic curvature is qualitatively consistent with the prediction of a numerical study, which investigated the geodesic curvature impact on the turbulent transport in the LHD configuration as well [13]. The zonal flow contribution with inwardly shifted configuration (R ax = 3.60 m) was also pointed out by a nonlinear gyrokinetic simulation [4].…”
Section: Evaluation Of Zonal Flow Effectsupporting
confidence: 84%
See 2 more Smart Citations
“…The zonal-flow effect significantly decreases with the geodesic curvature, whereas the scatter is large in the region of Z 1/2 /T < C 2 = 1.1 × 10 −2 . The dependence of the zonal-flow effect on the geodesic curvature is qualitatively consistent with the prediction of a numerical study, which investigated the geodesic curvature impact on the turbulent transport in the LHD configuration as well [13]. The zonal flow contribution with inwardly shifted configuration (R ax = 3.60 m) was also pointed out by a nonlinear gyrokinetic simulation [4].…”
Section: Evaluation Of Zonal Flow Effectsupporting
confidence: 84%
“…Therefore, turbulent transport level with the zonal flow can be calculated by only linear calculations. The zonal flow dependence on the geodesic curvature has been investigated with linear and nonlinear gyrokinetic simulations, in which the geodesic curvature was selectively modulated in the numerical simulations, and was verified for three different configurations such as the large helical device (LHD) NCSX-like, and axisymmetric configurations [13]. In tokamak geometry, the geodesic curvature tends to decrease with increasing elongation and increase with increasing triangularity [14].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[4][5][6] Plasma turbulence has been studied using gyrokinetics in both tokamak and stellarator geometry, where it has been found that the magnetic geometry can have a substantial influence on both the underlying microinstabilities 1,[7][8][9][10][11][12][13][14] and the transport levels in the saturated state. 8,12,13,[15][16][17] This is particularly true for the onset of TEMs, as the details of the magnetic geometry determine the locations of the magnetic minima and thus where trapped particles reside.…”
Section: Introductionmentioning
confidence: 99%